Bony Cubital Tunnel Syndrome: A Case Report of Heterotopic Ossification Causing Circumferential Ulnar Nerve Encasement at the Elbow and Review of Current Management. Issue 1 (January 2023) - Akhavan, Arya Andre; Catterall, Lauren Christina; Deune, Eagen Gene
Abstract : Background: Heterotopic ossification (HO) is a rare but known complication of brain and nerve trauma, orthopedic trauma, and burns. Nerve compression due to HO is extremely rare; "bony cubital tunnel syndrome, " or compression of the ulnar nerve at the elbow due to HO, is an unusual presentation that requires special considerations for treatment. Case Presentation: We present a 50-year-old man who presented to our hospital after vehicular polytrauma with associated car fire and prolonged extrication. He experienced extensive trauma, with all classically described risks for HO. He developed bony cubital tunnel syndrome, with ulnar neuropathy confirmed on electrodiagnostic studies, and underwent surgical decompression. Surgical decompression revealed circumferential encasement of the ulnar nerve in heterotopic bone, all of which was removed. He demonstrates appropriate recovery of nerve function. Literature Review: All perineural HO should be excised early to prevent nerve injury, because excision within 4 months of development is linked to improved functional outcomes. Measures to prevent nerve compression by HO are all associated with delayed wound or bone healing and should be considered on an individual basis.